A Novel Investigation and Hidden Effects of MHD and Thermal Radiations in Viscous Dissipative Nanofluid Flow Models - Ahmed, Naveed; Adnan,; Khan, Umar; Mohyud-Din, Syed Tauseef; Khan, Ilyas; Murtaza, Rashid; Hussain, Iftikhar; Sherif, El-Sayed M. (Frontiers in Physics, 2020)
Hidden effects of MHD and thermal radiations for a viscous dissipative nanofluids (Al2O3 − H2O and γAl2O3 − H2O) are taken under consideration. The models are formulated by implementing the suitable similarity transformations. Then, two models are discussed mathematically by using RK scheme together with shooting method. The results for flow regimes, coefficient of skin friction, thermophysical characteristics, and heat transfer coefficient are pictured and discussed comprehensively by changing the pertinent flow parameters. It is observed that the nanofluids velocity increases abruptly for higher Hartree pressure gradient. For assisting flow situation, the velocity F′(η) increases and abrupt decreasing behavior is examined for opposing flow case. The composition of Al2O3 − H2O, and γAl2O3 − H2O becomes more dense for high volume fraction therefore, drops in the velocity field is noted. The temperature of Al2O3 − H2O, and γAl2O3 − H2O rises rapidly by varying opposing flow parameter γ < 0 and high volume fraction ϕ. Also, the temperature β(η) declines abruptly for parameter λ.